Influence of Fuzheng Huayu Tablet (扶正化瘀片) on mental state and social function of patients with post-hepatitis B liver cirrhosis - Deng, Xin; Liang, Jian; Wu, Fa-sheng; Li, Yan-bo; Zhang, Ya-ping; Tang, Yan-fang (Chinese journal of integrative medicine, 2012)
Objective To observe the influence of Fuzheng Huayu Tablet (扶正化瘀片, FZHYT) on mental state and social activity of patients with post-hepatitis B liver cirrhosis (LC-HB). Methods Adopting grouped randomized double-blinded control method, 180 LC-HB patients in 3 research centers were distributed to 2 groups, the treated group and the control group, 90 in each group. Patients in the treated group were administered with FZHYT; while those in the control group treated with conventional therapy combined with placebo, the course for all patients were 6 months. Their mental state and social activity were evaluated before treatment, after 3 months’ treatment and at terminal of the 6-month therapeutic course by estimating with Zung self-rating anxiety scale (SAS), self-rating depression scale (SDS) and social deficit screening scale (SDSS). Additionally, the basic demographic materials, liver function, cirrhosis index, hepatic and splenic images, blood coagulation function, etc. in the patients were tested and compared as well. Results As compared with before treatment, the normal rate of SAS and SDS scores increased and the social deficit rate decreased in the treated group significantly after treatment, showing statistical significance ( P <0.05 or P <0.01); while in the control group, change was only shown in the social deficit ( P <0.01), inter-group comparisons after treatment showed significant differences in all the three indexes ( P <0.05 or P <0.01). Additionally, after treatment, levels of liver function, cirrhosis, blood coagulation function and splenomegaly in the treated group were all improved significantly P <0.05 or P <0.01), and the improvements were better than those in the control group ( P <0.01) in levels of total bilirubin (TBIL), albumin (ALB), type IV collagen (IV-C), prothrombin time (PT), prothrombin activity (PTA). Conclusion Most patients of LC-HB have mental disturbance and social activity deficit, which could definitely be improved by intervention with Chinese FZHYT.